Climate Change and Political Participation: Evidence from India - Amrit Amirapu; Irma Clots-Figueras; Juan Pablo Rud (Institute of Labor Economics (IZA), 2022)
We study the effects of extreme temperature shocks on political participation using data from Indian elections between 2009 and 2017. Taking advantage of localized, high-frequency data on land surface temperatures, we find that areas with greater cumulative exposure to extreme temperatures experience an increase in voter turnout and a change in the composition of the pool of candidates who stand for election. As a consequence, electoral outcomes are affected. We provide evidence that our results are driven by the negative effect of climate change on agricultural productivity. First, we show that the results are strongest in areas with a larger rural population. Second, we show that there is a non-monotonic relationship between temperatures and turnout which closely mirrors the relationship between temperatures and agricultural productivity. We also find that, following temperature shocks, winning candidates are more likely to have an agricultural background. Finally, we show that politicians with an agricultural background invest more in irrigation, which mitigates the effects of high temperatures, on both agricultural production and on turnout. Our paper provides new evidence about the ways in which political agents in developing countries (including both voters and candidates) may respond to climate change via political channels.
Keywords: O13; P48; Q54; 330; climate change; political economy; voter turnout